2017
DOI: 10.1016/j.placenta.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

The core transcriptome of mammalian placentas and the divergence of expression with placental shape

Abstract: Introduction The placenta is arguably the most anatomically variable organ in mammals even though its primary function is conserved. Method Using RNA-Seq, we measured the expression profiles of 55 term placentas of 14 species of mammals representing all major eutherian superordinal clades and marsupials, and compared the evolution of expression across clades. Results We identified a set of 115 core genes which is expressed (FPKM ≥ 10) in all eutherian placentas, including genes with immune-modulating prope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…Although the placenta is anatomically variable across mammalian species, a core transcriptome of around 115 genes can be identified that are critical to the function of the placenta across species (Armstrong et al 2017 ). Predominant amongst these are members of the annexin family, AnxA2, AnxA1 and AnxA5, arguing for the evolutionary importance of annexins (Armstrong et al 2017 ). Annexins are also known as ‘placental anti-coagulant proteins’ and they have been estimated to constitute up to 2% of the total placental membrane proteins (Buhl et al 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the placenta is anatomically variable across mammalian species, a core transcriptome of around 115 genes can be identified that are critical to the function of the placenta across species (Armstrong et al 2017 ). Predominant amongst these are members of the annexin family, AnxA2, AnxA1 and AnxA5, arguing for the evolutionary importance of annexins (Armstrong et al 2017 ). Annexins are also known as ‘placental anti-coagulant proteins’ and they have been estimated to constitute up to 2% of the total placental membrane proteins (Buhl et al 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 14% (N=61/447) of the genes we identified as upregulated in human were previously annotated in other comparative studies as specifically expressed or upregulated in human placenta compared to many distantly-related species (Hou et al 2012;Armstrong et al 2017). However, since these studies relied on the comparison of placental gene expression across numerous distantly-related species, they were limited in the number of orthologous genes eligible for differential expression comparison.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian placenta shows great diversity across species in its morphology and tissue organization, mechanisms of implantation and invasion, and physiological regulation [ 2 , 3 ]. Even trophoblast cells, the cellular building blocks of the placenta, bear little morphological or molecular resemblance across species [ 4 ]. Current theories suggest that life history changes and/or parent–offspring conflicts over maternal resources promoted rapid evolution of the placenta [ 5 , 6 ].…”
Section: The Rapidly Evolving Placentamentioning
confidence: 99%